Rush : a novel - Patton, Lisa (St. Martin's Press, 2018)
Cali Watkins possesses all the qualities sororities are looking for in a potential new member. She<U+2019>s kind and intelligent, makes friends easily, even plans to someday run for governor. But her resume lacks a vital ingredient. Pedigree. Without family money Cali's chances of sorority membership are already thin, but she has an even bigger problem. If anyone discovers the dark family secrets she's hiding, she<U+2019>ll be dropped from Rush in an instant. When Lilith Whitmore, the well-heeled House Corp President of Alpha Delta Beta, one of the premiere sororities on campus, appoints recent empty-nester Wilda to the Rush Advisory Board, Wilda can hardly believe her luck. What<U+2019>s more, Lilith suggests their daughters, both incoming freshman, room together. What Wilda doesn<U+2019>t know is that it's all part of Lilith<U+2019>s plan to ensure her own daughter receives an Alpha Delt bid<U+2015>no matter what. For twenty-five years, Miss Pearl<U+2015>as her “babies” like to call her<U+2015>has been housekeeper and a second mother to the Alpha Delt girls, even though it reminds her of a painful part of her past she<U+2019>ll never forget. When an opportunity for promotion arises, it seems a natural fit. But Lilith Whitmore slams her Prada heel down fast, crushing Miss Pearl<U+2019>s hopes of a better future. When Wilda and the girls find out, they devise a plan destined to change Alpha Delta Beta<U+2015>and maybe the entire Greek system<U+2015>forever.